1997
DOI: 10.1002/(sici)1098-240x(199706)20:3<219::aid-nur5>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing choices: Patients' experiences with making treatment decisions

Abstract: Because little is known about the perceptions of patients who make health care decisions under potentially life-threatening conditions, a grounded theory approach was utilized to describe decision making from the patient's perspective. Eighteen respondents, aged 26 to 81, with diagnoses of heart disease, renal failure, or cancer were interviewed shortly after making a decision regarding treatment of their conditions and again about 1 month later. Respondents reported that their decisions to accept treatment we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…Kelly-Powell (1997) found in her study that decisions to accept treatment are personalised to correspond with the patients’ view of themselves within the context of their life stories. Thorne et al (2003) explained how people with chronic disease come to rely heavily on a skill-base founded on personal experience with the disease within the context of their unique lives rather than standardised knowledge alone.…”
Section: Discussionmentioning
confidence: 99%
“…Kelly-Powell (1997) found in her study that decisions to accept treatment are personalised to correspond with the patients’ view of themselves within the context of their life stories. Thorne et al (2003) explained how people with chronic disease come to rely heavily on a skill-base founded on personal experience with the disease within the context of their unique lives rather than standardised knowledge alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous health-related experiences or familiarity with treatment options can influence treatment choice (Kelly-Powell, 1997; Mazur & Merz, 1996). Using Grounded Theory methodology, Berry and colleagues uncovered a set of related, meaningful factors among men with localized prostate cancer (stage I or II), which included past experience with cancer (Berry, et al, 2003).…”
Section: Patient-centered Factors That Affect Cancer Treatment Decisimentioning
confidence: 99%
“…Similarly, Kelly-Powell (1997) investigated patients' experiences of the decision-making process and found that people make "personalized choices." Patients made decisions based on their perception of past experiences and a wish to maintain a current image of self as well as images of the future.…”
Section: Review Of the Literaturementioning
confidence: 99%